Customer Relationship Management in Asia/Pacific Cruise Industry - Liu, Xiao Meng (2006)
ABSTRACT This study has demonstrated Customer Relationship Management (CRM) in the cruise industry is vital for its long-term success. The globalization of business has directly influenced the overall business strategy of cruise companies worldwide. Many cruise companies are consolidating into a few large corporations through merger and acquisition. These big cruise companies are extending their businesses to every corner of the world, with increasing bigger ships providing high volume passenger capacity. This has greatly changed the landscape and market competition in the cruise industry.